PERBEDAAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL BAWANG PUTIH (Allium ascalonicum L.) DIDATARAN RENDAH - Anggra Saputra; Gusni Yelni (Jurnal Sains Agro, 2020)
The research was conducted with the goal of evaluating the spacing effect and having the right spacing for growth and yield of garlic (Allium ascalonicum L.) in lowland ultisol. This research used a 5-treatment Randomized Block Model (RBD), namely: J1 (10 x 10 Spacing), J2 (10 x 15 Spacing), J3 (15 x 20 Spacing), and J4 (20 x 20 Spacing). The observed variables in this analysis were plant height (cm), number of leaves (strands), tuber / plant diameter (cm), tuber-wet weight per clump (g), tuber-wet weight per plot (g) and production (tons / ha). The effect of spacing on observed variables is calculated, then evaluated using variance analysis (ANOVA). If it has a major impact, the Ducan Multiple Range Te shall continue.The findings showed that specific plant spacing used influenced the tuber wet weight per plot (g) and output (tons / ha) considerably. J1 treatment (10 x 10 Spacing) is the right spacing for tuber wet weight per plot (g) and garlic production (tons / ha) in lowland ultisols (Allium ascalonicum L.)Keywords: Plant Spacing, Garlic, Growth and Yield